Performance assessment of StandardTM Q COVID-19 Ag Test in Ouagadougou, Burkina Faso - Abdou Zoure; Henri Ouedraogo; Serge Soubeiga; Tegwinde Compaoré; Sylvie Zida; Oumarou Ouedraogo; Dinanibè Kambiré; Dezemon Zingue; Charlemagne Dabiré; Alidou KAGAMBEGA; Charles Sawadogo; Zakariya Yabre; et al. (Microbes and Infectious Diseases, 2023)
Background: Many rapid antigen kits for SARS-CoV-2 detection have been developed and the results interpreted usually within 30 minutes. Antigen tests are recommended to be used in areas where access to the PCR method is limited, as is the case in Burkina Faso. The aim of this study is to assess the performance of "Standard TM Q COVID-19 Ag Test " in the detection of SARS-CoV-2 antigen. Methods: The evaluation was performed using swabs samples collected between January 26 and March 31, 2021, from 201 subjects previously diagnosed by RT-PCR.  The performance of the rapid test “Standard TM Q COVID-19 Ag Test was compared to the RT-PCR test “STANDARD M nCoV real-time detection kit”. Results: Of these 201 samples, 16 were positive for the COVID-19 RT-PCR, and 185 were negative. The sensitivity of the "Standard TM Q COVID-19 Ag Test" was 100% (IC95%: 34.24- 100) in symptomatic subjects with a symptom onset time of 1 to 5 days. This sensitivity decreased to 66.67% (IC95%: 20.77- 93.85) in symptomatic subjects with a symptom onset time of 1 to 7 days. The specificity, it was 95% (IC95%: 83.5-98.62) in all symptomatic subjects and 93.75% (IC95%: 79.85-98.2) in subjects whose symptoms appeared between 1 and 5 days. Conclusion: The " Standard TM Q COVID-19 Ag Test " was better in subjects with delayed symptoms up to 5 days. However, this kit was not suitable for COVID-19 detection in asymptomatic subjects.